Translation and cross-cultural adaptation of the Headache Screening Questionnaire into Brazilian Portuguese - Lopes, Erika Plonczynski; Oliveira, Ana Beatriz; Gonçalves, Daniela Aparecida Godoi [UNESP]; Meer, Hedwig Aleida van der; Visscher, Corine Mirjam; Speksnijder, Caroline M.; Calixtre, Letícia Bojikian [UNESP] (Elsevier, 2022)
Background: The Headache Screening Questionnaire (HSQ) was created and validated to enable health professionals to screen for migraine and tension-type headaches. Objectives: The objective of this study was to translate and cross-culturally adapt the HSQ, creating the Brazilian version of the HSQ (HSQ-BR). Design: This was a cross-sectional study. Method: The Brazilian version of the HSQ was developed following the processes of translation, synthesis, back-translation, expert committee review, and pre-testing. The translation phase involved two independent translators whose mother language was Brazilian Portuguese and who also were fluent in Dutch. The back-translation phase involved two independent translators whose mother language was Dutch and who also were fluent in Portuguese. The expert committee based their decisions on semantic, idiomatic, experiential, and conceptual equivalences. To verify the comprehension of the questionnaire, 60 subjects (73.3% women) with headaches with a mean age of 32.8 ± 12.0 years, participated in the pre-test phase. Results: During the translation process, some terms and expressions were changed to obtain cultural equivalence to the original HSQ. The process of translation and cross-cultural adaptation of the HSQ to the Brazilian culture and Portuguese language, including its scoring algorithms for migraine and tension-type headache, was successfully concluded, as the comprehension of each item of the questionnaire was over 90% on the pre-test. Conclusion: The HSQ-BR has been created.
Keywords: Headache disorder; Primary headache disorders; Questionnaire